Parent and Adolescent Thoughts About Suicide Risk Screening in Pediatric Outpatient Settings. Issue 3 (3rd July 2022) - Bradley-Ewing, Andrea; Sullivant, Shayla A.; Williams, David D.; Lanzillo, Elizabeth; Aguinaldo, Laika; Wharff, Elizabeth; Horowitz, Lisa M.; Goggin, Kathy
Abstract: Suicide rates among adolescents in the United States continue to climb and many at-risk youths are undetected. Screening for suicidal thoughts has become the primary approach to identify those at risk, but no studies have assessed reactions to its deployment in pediatric outpatient settings. This mixed-method study assessed parents' and adolescents' thoughts about suicide risk screening in non-psychiatric, pediatric outpatient specialty settings. As part of a multi-site measurement validation study, adolescents ( n = 269; ages 10–21) and parents ( n = 246) at pediatric specialty clinics in the Midwest completed a survey regarding thoughts about suicide risk screening. Data were collected on tablet computers and transcribed verbatim. Three study team members independently coded transcripts of open-ended responses to identify major themes, and frequency data were analyzed using StataSE 15.1. Inter-rater agreement was substantial (Fleiss' Kappa ranged 75–86%). Parents (55% 41–50 years of age, 20% male, 80% White) and adolescents (Mean age = 14.3, 50% male, 77% White) agreed medical providers should screen adolescents for suicide risk (93% and 88%, respectively). Majority of parents indicated that the pediatric outpatient setting is appropriate for suicide risk screening. Major themes included the important role of providers in identifying at-risk youth, the potential for screening to prevent suicides, and concerns about iatrogenic risk and misdiagnosis. Most parents and adolescents support screening for suicide risk in pediatric outpatient settings. Nevertheless, some have concerns about the screening process and implications. As suicide risk screening becomes standard practice in adolescent care, it's critical to develop screening processes that maximize comfort and address concerns.